Germany - Two Demographically Different States? - Szymańska, Daniela; Środa-Murawska, Stefania; Biegańska, Jadwiga (Bulletin of Geography. Socio-economic Series, 2008)
The paper is an attempt of an answer how belonging to different political, economical and cultural structures has influenced diverse population processes and structures and their spatial diversity. As an example to the research of these phenomena there was chosen Germany that until 1990 were two separated socio-political and economical formations (the German Democratic Republic (GDR) and the Federal Republic of Germany FRG). This state, with a population number about 82 millions presently, as it turns out - besides passage of time - is characterized all the time by some diversity of procreation behaviors, population processes and structures in the Eastern (Ost) and the Western part (West) of Germany. It is claimed, the structures are going to some similarities, but the 15 years period (1990-2005) was too short to level all stated demographical differences and trends (1).